Cost analysis of rice milling: a case study of 7 rice mills in Malaysia - Chung, Bonhee; Mohamed Arshad, Fatimah; Mohd Noh, Kusairi; Sidique, Shaufique Fahmi (Emerald Group Publishing Limited, 2016)
Purpose - The purpose of this paper is to examine the long-run profitability of rice milling operation in Malaysia and see how sensitive it is to changes in paddy purchases, rice recovery ratio and paddy price.